Pain Sensitivity and Psychiatric Comorbidities in Chronic Pancreatitis Patients With and Without Pain: Past Experience Matters - Anna E. Phillips; Benjamin L. Bick; Mahya Faghih; Dhiraj Yadav; Asbjørn M. Drewes; Vikesh K. Singh; Søren S. Olesen (Gastro Hep Advances, 2022)
Background and Aims: Pain is the primary symptom of chronic pancreatitis (CP) and has been associated with abnormal pain processing and psychologic distress. Little is known about these phenomena in patients with painless disease. The aim of this study was to characterize patterns of pain processing and psychologic distress in patients with primary painless vs painful CP. Methods: This was a cross-sectional multicenter study of 235 patients with definitive CP. Patients were categorized based on current and past pain history; current pain (79%), no current (but prior) pain (11%), and painless CP (10%). Demographic information and clinical data including symptoms of anxiety and depression using the Hospital Anxiety and Depression Scale were collected. All patients underwent quantitative sensory testing to assess patterns of pain processing. Results: A total of 235 patients (57% males, mean age 53.9 ± 14.0 years, 41% alcohol etiology) were included. Compared to patients with painless CP, enhanced pain sensitivity was observed in both patients with current pain (odds ratio [OR] 3.29; 95% confidence interval [CI] [1.11–9.77], P = .032) and no current pain (OR 4.07; 95% CI [1.10–15.03], P = .035). Patients with current pain also had increased depression prevalence compared to patients with painless CP (OR 6.15; 95% CI [1.28–29.41], P = .023), while no difference was seen for patients with no current pain (OR 1.24; 95% CI [0.19–8.26], P = .824). Conclusion: Total absence of pain in CP is associated with normal pain processing and low prevalence of psychologic distress, whereas patients with prior pain experience appear to have persistent and enhanced pain sensitivity even in the absence of clinical pain and psychologic distress.